Strategi Pengembangan Bisnis Wisata Syariah Pada Masyarakat Pluralis di Kabupaten Ponorogo - Ika Susila Wati (International Journal Ihya' 'Ulum al-Din, 2020)
The development of sharia tourism has a multidimensional impact. One of them is employment and poverty alleviation, especially in Ponorogo, considering that is the 11th largest city contributing to Indonesian migrant workers. The development of the sharia tourism business is increasingly attractive, because the Ponorogo community is a pluralistic society, which embraces a variety of cultures, religions and creeds. So that the role of local government as a leading sector is needed to determine the planning and development of regional sharia tourism. For that we need the right strategy in the development of Islamic tourism in accordance with the characteristics of Ponorogo. In the formulation of the right strategy, data from Muslim, non-Muslim and local government communities is needed. The data is analyzed by the SWOT technique which is supported by internal and external factors. With the result has the potential in the development of sharia tourism considering there are still many natural tourism objects that have not been touched and developed by the community or local government. The development of Islamic tourism is approved by Muslim, non-Muslim communities, while maintaining their respective religious sites. The strategy generated from the SWOT analysis formed a map diagram of the development of sharia tourism business in Ponorogo.